Constitutional Court’s Role in Regional Head Election Disputes: Substantive Justice and Voting Threshold Challenges - Fathullah, Fathullah; Muhtar, Mohamad Hidayat; Yustiana, Yustiana; Saharuddin, Saharuddin; Syahbana, Rio Akmal (Universitas Negeri Gorontalo, 2025)
This study examines the Constitutional Court's authority in resolving regional head election disputes, focusing on its role in ensuring substantive justice and the implications of the vote threshold in Article 158 of the Regional Head Election Law on candidates' constitutional rights. The research employs a normative legal method, utilizing a statutory approach to analyze the Court’s jurisdiction, a case approach to assess key decisions, and a conceptual approach to evaluate the principles of substantive justice in electoral disputes. Primary legal sources include the 1945 Indonesian Constitution and Constitutional Court rulings, while secondary sources consist of scholarly literature, legal commentaries, and tertiary legal references. The findings reveal that the Constitutional Court has played a pivotal role in upholding democratic principles by setting aside formalistic constraints such as the vote threshold when structured, systematic, and massive violations significantly impact election outcomes. However, this approach raises concerns regarding the consistency of judicial rulings and legal certainty. Additionally, the study highlights that Article 158 often limits candidates’ access to legal remedies, restricting their ability to contest elections despite substantial evidence of electoral fraud. The study contributes to the academic discourse on electoral justice by demonstrating how legal formalism can undermine substantive justice in democratic processes. It recommends revising Article 158 to introduce an exception mechanism that balances procedural efficiency with fairness, thereby enhancing the legitimacy and integrity of regional head elections. This reform is essential to ensure a more equitable electoral dispute resolution system that safeguards both democratic accountability and legal certainty.